2015
DOI: 10.1149/2.0781508jes
|View full text |Cite
|
Sign up to set email alerts
|

The Unexpected Role of Benzotriazole in Mitigating Magnesium Alloy Corrosion: A Nucleating Agent for Crystalline Nanostructured Magnesium Hydroxide Film

Abstract: Benzotriazole (BTA), an effective corrosion inhibitor for Cu or Cu-containing Al alloys, was added to 0.1 M NaCl to study its potential role in suppressing corrosion of the commercial Mg alloy, AMlite. In particular, the impact of pH and BTA concentration was investigated, indicating that BTA was effective at restricting corrosion of AMlite in weakly alkaline NaCl solution, i.e. pH 10.0. The degree of the protection afforded was a function of BTA concentration. The best corrosion inhibition was found in the Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 49 publications
(96 reference statements)
0
13
0
Order By: Relevance
“…As a result, corrosion sites and the solution in the pores of the PEO coating will be alkalised. According to Wang et al [53], protection for the Mg alloy because of the loose structure ( Fig. 17(a,b)), which can be identified by the significant decrease in impedance after 4 h of immersion in NaCl solution ( Fig.…”
Section: Response To Damage Induced By Anodic Polarisationmentioning
confidence: 99%
“…As a result, corrosion sites and the solution in the pores of the PEO coating will be alkalised. According to Wang et al [53], protection for the Mg alloy because of the loose structure ( Fig. 17(a,b)), which can be identified by the significant decrease in impedance after 4 h of immersion in NaCl solution ( Fig.…”
Section: Response To Damage Induced By Anodic Polarisationmentioning
confidence: 99%
“…Although copper does not react with hydrochloric acid, because the reduction potential of copper is higher than that of hydrogen, copper specimens immersed in 0.5 M HCl solution [66,67,68] BTAH has a pKa of 8.4 at 25 °C in water [5,27,69,71,72], which means that at pH values lower than pKa the prevalent species is BTAH in its neutral form; at pH < 1 is in the protonated form, BTAH2 + ; above 8.4 is in the anionic form, BTA -, instead. Therefore at our experimental conditions BTAH is prevalent as a solvated neutral species.…”
Section: Discussionmentioning
confidence: 99%
“…Benzotriazole (BTA), included in Ardrox 3961, has been studied as an inhibitor for Cu, Al, Mg and steels. [30][31][32][33][34][35][36][37][38] For example, Abu-Baker et al [38] reported that BTA was an effective corrosion inhibitor for Cu and 5% tin bronze in 0.5 M NaCl + 0.1 M CuCl 2 solution, while Žerjav and Milošev [31] found that (a) BTA accelerated Cu corrosion in simulated urban rain and (b) inhibited corrosion when combined with stearic acid. BTA was found to inhibit Cu corrosion by the formation of BTA-Cu and BTA-Cu(O) complexes.…”
Section: Cicsmentioning
confidence: 99%
“…[37,39] Guo et al [40] found that BTA was effective for anodised AZ91B. Wang et al [35] found that BTA was effective by the formation of a dense, highly crystalline Mg(OH) 2 film. In contrast, Lamaka et al [34] found that BTA accelerated the corrosion of pure Mg and the Mg alloys WE43, ZE41 and EV31.…”
Section: Cicsmentioning
confidence: 99%